Optimality and Duality for Invex Nonsmooth Multiobjective programming problems - Kim, Do Sang; Schaible, Siegfried (Optimization, 2004)
We consider nonsmooth multiobjective programming problems with inequality and equality constraints involving locally Lipschitz functions. Several sufficient optimality conditions under various (generalized) invexity assumptions and certain regularity conditions are presented. In addition, we introduce a Wolfe-type dual and Mond-Weir-type dual and establish duality relations under various (generalized) invexity and regularity conditions.